Special approaches of engineering-geophysical operations at high level of industrial noise - N., Antonovskaya G.; Lu, Ngo Thi; K., Kapustian N.; M., Basakina I.; Y., Afonin N.; V., Danilov A.; A., Moshkunov K.; Hang, Phung Thi Thu (Vietnam Journal of Marine Science and Technology, 2017)
The capabilities of the complex of seismic methods, which are suitable for inspecting of large strategic objects are presented. In this paper next tasks for the dam investigation and the upper part of the section of its area were considered: probing of the construction state of the dam; characterization of the dam connection to the river banks; identification of possible tears in the proximity of a day surface; identification of possible soil state changes that are caused by technogenic-originating impact or geologic processes.